Infographic of the zero deforestation and low greenhouse gas (GHG) emissions business model in oil palm from Oleaginosas Amazonicas and the Central Committee of Palm Growers of Ucayali - Ivanova, Yovita; Lema, Sebastián; Tristán Febres, María Claudia; Sánchez Choy, José G.; Orjuela, Felipe; Quintero, Marcela; Castro, Juan Pablo (2022)
Infographic of the zero deforestation and low Greenhouse Gas (GHG) emissions business model of the Oleaginosas Amazónicas and the Central Committee of Palm Growers of Ucayali of the palma oil value chain in Peru. It has been produced within the framework of the IKI project "Business models to address the drivers of deforestation in Peru" developed in the Ucayal region